1984
DOI: 10.2337/diacare.7.6.528
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Treatment of Diabetic Ketoacidosis in a Community Population

Abstract: We evaluated the epidemiology of diabetic ketoacidosis in the period 1960-1979. In Frederiksborg County, Denmark, the incidence of ketoacidosis at the county hospital increased from 60 per 100,000 in the period 1943-1963 to 120 per 100,000 in the period 1960-1979. In the investigation period we found an increasing incidence confined to urban areas. Precipitating factors were not somatic in 53% of the cases. Patients in the lowest social class (V) were in a higher risk group, experiencing ketoacidosis more ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
4
6

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 9 publications
3
33
4
6
Order By: Relevance
“…Although it has been repeatedly shown that infection is a common precipitating event in DKA and HHS in this country and abroad (4,12), recent studies suggest that omission of insulin or undertreatment with insulin may be the most important precipitating factor in urban African-American populations (5,26). Table 3 summarizes various studies (2,5,6,(27)(28)(29)(30) describing precipitating events for DKA.…”
Section: Precipitating Events -mentioning
confidence: 99%
See 2 more Smart Citations
“…Although it has been repeatedly shown that infection is a common precipitating event in DKA and HHS in this country and abroad (4,12), recent studies suggest that omission of insulin or undertreatment with insulin may be the most important precipitating factor in urban African-American populations (5,26). Table 3 summarizes various studies (2,5,6,(27)(28)(29)(30) describing precipitating events for DKA.…”
Section: Precipitating Events -mentioning
confidence: 99%
“…Recent studies that have emphasized the use of standardized written guidelines for therapy have demonstrated mortality rates Ͻ5% in DKA and ϳ15% in HHS (6,9,10,(12)(13)(14)(15)(16)214). The majority of deaths have occurred in patients Ͼ50 years of age because of concomitant life-threatening illnesses, suggesting that further major decreases in mortality rates may not be attainable based on treatment of DKA alone (9).…”
Section: Resource Utilization Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The annual incidence of DKA among subjects with type 1 diabetes is between 1% and 5% in European and American series [6][7][8][9][10] and this incidence appears to have remained relatively constant over the last decade in Western countries. Episodes of DKA are more common in younger than older subjects and are twice as common in females than males.…”
Section: Epidemiologymentioning
confidence: 99%
“…The diagnoses of HNKHC and DKA are clinically very easy to confuse, [10][11][12][13][14] because both of them are acute diabetic complications caused by a lack of insulin secretion. The difference is that HNKHC is common in the elderly, and dehydration, hyperosmosis, and hyperglycemia is more serious, but without or with only mild ketoacidosis.…”
mentioning
confidence: 99%